Drug Nanocrystals in Oral Absorption: Factors That Influence Pharmacokinetics - Luiza de Oliveira Macedo; Jéssica Fagionato Masiero; Nádia Araci Bou-Chacra (MDPI AG, 2024)
Despite the safety and convenience of oral administration, poorly water-soluble drugs compromise absorption and bioavailability. These drugs can exhibit low dissolution rates, variability between fed and fasted states, difficulty permeating the mucus layer, and P-glycoprotein efflux. Drug nanocrystals offer a promising strategy to address these challenges. This review focuses on the opportunities to develop orally administered nanocrystals based on pharmacokinetic outcomes. The impacts of the drug particle size, morphology, dissolution rate, crystalline state on oral bioavailability are discussed. The potential of the improved dissolution rate to eliminate food effects during absorption is also addressed. This review also explores whether permeation or dissolution drives nanocrystal absorption. Additionally, it addresses the functional roles of stabilizers. Drug nanocrystals may result in prolonged concentrations in the bloodstream in some cases. Therefore, nanocrystals represent a promising strategy to overcome the challenges of poorly water-soluble drugs, thus encouraging further investigation into unclear mechanisms during oral administration.